POLA PEMBIASAAN ORANG TUA MENDIDIK ANAK MEMBACA AL-QUR’AN DALAM RUMAH TANGGA DI PERUMAHAN BUKIT DEWA RESIDEN RT 03 RW 01 KELURAHAN SUMUR DEWA KECAMATAN SELEAR KOTA BENGKULU - Fajar Kurniawan (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2019)
This study aims to To reveal the parenting pattern  of parents  in educating their children in reading the Qur’an in their family. This research  is a field research  (field research), with descriptive qualitative method. Data collection was conducted using unstructured interviews, selected observation and documentation. Data processing with editing, classification, data analysis and conclusion.  The results showed  that: 1) The pattern  of parents’  habituation to educate children  in reading  the Qur’an  in Resi- dential Bukit Dewa Resident RT 03 RW 01 Village Sumur Dewa District Selebar Kota Bengkulu runs quite well, educate children read  the Qur’an  by sending  children to study in the mosque and  bring teachers  to study home.  The patterns  used are through direct approach, exemplary  patterns, patterns  of habituation, patterns  of advice, patterns  of punishment and giving rewards.  2) Example  of parent  to educate their children in reading  the Al-Qur’an has not been  realized properly.  Among the lesser causes are: first the laziness of the parents  themselves, second  because of busy in the work of parents. 3) Form of evaluation provided by parents  in habituation to educate children reading  the Al-Qur’an has been  going pretty well. First of all with praise and  flat- tery, second  by giving gifts, third by giving punishment. 4) Parental  obstacles  in educating children reading  the Qur’an include: first factor self, second  the number of tasks from school, third factor of parents, fourth environmental factor of society